Toxic effects of mercuric chloride on DNA damage, hematological parameters and histopathological changes in common (carp Cyprinuscarpio): 1Abdulmotalib J. Alrudainy; 1Sanaa A. Mustafa and 2Maher A. Abdulaziz - Alrudainy, Abdulmotalib J. (The Iraqi Journal of Veterinary Medicine, 2014)
The present study aimed to evaluate the effects of mercuric chloride (HgCl2) at different levels of biological organization in common carp Cyprinuscarpio following exposure for 30 days to a range of environmentally levels of mercuric chloride (0.01 and 0.02 mg L-1) and recovery for 3 weeks. Prior to evaluation of genetic damage (determined in erythrocytes using comet assay), enzymatic activity (ALT and AST), hematological parameters and histopathological examination of gill.The maximum tolerated concentration also determined which was found to be 1.63 µg l-1 above which complete mortality over the exposure period was observed. The results indicated that there was a strong induction for DNA damage at high level of Hg. Hematological indices indicated significantly (P≤0.05) increased in Hb, RBCs and Hct value in Hg treatment groups compared to control group after 15 and 30 days exposure. Histopathological examination showed distinct abnormalities in secondary lamellae of gill including epithelial lifting, fusion of the secondary lamellae and necrosis. The present findings suggest that exposure to a low concentration (0.01mg L1) of inorganic mercury can cause significant changes in DNA, hematological parameters and also could cause histopathological changes. Therefore, estimation of these indices could provide a useful indicator for monitoring water bodies pollution.